Linear programming model for production costminimization at a rice crop products manufacturer (2021)
Companies in general must establish processes that generate profitabil-ity at lower costs. Manufacturing of rice crop protection products requires majorinvestments and resource planning, including infrastructure, raw materials, tech-nology, human resources, tests and trials, among others, which represents a majorchallenge. This paper proposes a methodology that aims to minimize productioncosts taking different factors into consideration. The first section identifies anddescribes the variables required for modeling. In the second section a linear pro-gramming model is formulated to determine the optimal function in terms of costreduction. Lastly, the model was applied at a real company, producing satisfactoryresults in terms of an improved production plan and an 11% cost reduction, whileenabling viewing the variables with greatest impact, such as storage and shift pro-gramming, with cost reductions of 68% and 44%, respectively. The purpose is toassist companies in this industry in applying mathematical programming modelsto solve problems and enable better resource planning to improve profitability